SUITABILITY OF ICE STORED MACKEREL AND SARDINE FOR CANNING - MADHAVAN, P; BALACHANDRAN, K K; CHOUDHURI, D R (Fishery Technology, 2025)
The paper reports the re ults of studies. on ice storage and subsequent canning of mackerel (Rastrelliger l<anagurta) and Sardines (Sardine/la /ongiceps) and the effect of such storage on the quality of the canned product prepared out of them. The changes in the physical and chemical characteristics during ice st.orage are determined and correlated with the:quality of the finished product